USING PHONETIC TRANSCRIPTION TO IMPROVE STUDENTS’ PRONUNCIATION SKILLS - Bambang Irawan; Muhammad Ahsan Tampubolon (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
For EFL students especially the students of English Letters Department at Pamulang University, mastering English is something challenging. There are several problems which they face in learning English. One of the most crucial problems is pronunciation. Hence, appropriate teaching methods such as using phonetic transcription are needed to help the students to improve their pronunciation. This research focused on using phonetic transcription to improve the pronunciation skills of the fourth semester students of English Letters Department of Pamulang University. It was aimed to reveal if the utilization of phonetic transcription was able to improve the students’ pronunciation. It was also aimed to figure out how phonetic transcription improved the students’ pronunciation. This research implemented Classroom Action Research which was carried out from February until April 2020. There were two cycles in this research and each cycle consisted of three meetings. In collecting the data, the writers used field notes, interviews and tests. The average of the students’ score in the pre-cycle and cycle 1 were 59,86 and 66,07 which were still lower  than 75 as the target. In the cycle 2, the average of the students’ score was 75,56 which was higher than 75. Based on the results of the study, it can be concluded that phonetic transcription was able to improve the students’ pronunciation. Phonetic transcription had role in improving both segmental and supra segmental features of the students’ pronunciation.